Efeitos interativos do canabidiol sobre o comportamento cognitivo, comportamento emocional e neuroplasticidade hipocampal de camundongos - Schiavon, Angélica Pupin (2014)
The aim of this study was to evaluate the interactive effects of cannabidiol (CBD) on cognitive behavior, emotional behavior and hippocampal neuroplasticity in mice. In the first chapter, we investigated whether CBD protects against hippocampal neurodegeneration and cognitive prejuízos induced by cerebral ischemia in adult mice. They were submited to a bilateral common carotid artery occlusion (BCCAO) model and tested in the Morris water maze (MWM) 7 days later. CBD (3, 10, and 30 mg/Kg) was administered 30 min before, 3, 24, and 48 h after BCCAO. After behavioral testing, the brains were removed and processed to evaluate hippocampal cell survival and degeneration using Nissl staining and FluoroJade C (FJC) histochemistry, respectively. Changes in cellular proliferation and neurogenesis were analyzed by the Ki-67 and doublecortin (DCX) immunostainings, respectively. Astroglial response and dendritic integrity of neurons were examined by the glial fibrillary acidic protein (GFAP) and microtubule-associated protein 2 (MAP2) immunostainings, respectively. CBD (3-30 mg/kg) improved spatial learning performance in BCCAO mice. The Nissl and FJC staining results showed a decrease in hippocampal neurodegeneration after CBD (10 and 30 mg/kg) treatment. CBD repeated treatment showed a dual effect in cell proliferation and neurogenesis, by increasing and decreasing the number of Ki-67- and DCX-positive cells at the subgranular zone (SGZ) of the hippocampal dentate girus (DG) in ischemic animals. GFAP immunoreactivity was also decreased in ischemic mice treated with CBD (30 mg/kg). These findings suggest a protective effect of CBD on neuronal death induced by ischemia and indicate that CBD might exert beneficial therapeutic effects in brain ischemia. In the second chapter, we investigated the effects of acute or repeated CBD administration on unstressed mice emotional behavior and its neurogenesis relation. Mice received CBD (3, 10 or 30 mg/Kg) or vehicle daily intraperitoneally (i.p.) once one hour before behavioral testing. To evaluate the effects of repeated CBD effects, mice received CBD (3 or 30 mg/Kg) or vehicle, (i.p.), during 15 consecutive days. Twenty-four hours, 11 or 21 days after the end of repeated CBD treatment, the animals were sacrificed and had their brains removed for subsequent Ki-67, BrdU, DCX and GFAP immunostainings analysis. Acute administration of CBD revealed an anxiolytic-like effect in the elevated plus maze (EPM) and open field (OF) models as well as antidepressant-like effect in tail suspension test (TST). None changes in animals locomotor activity was observed. CBD repeated treatment, however, showed only the antidepressant-like effect. Twenty-four hours after the CBD (3 mg/Kg) repeated treatment demonstrated an increase in cell proliferation at the SVZ and SGZ (BrdU- and Ki-67-positive cells), whereas, a significant increase of DCX young neurons were detected only in SGZ. Eleven days after the CBD repeated treatment, a significant increase of BrdU- and DCX-positive cells were detected in the hippocampal SGZ. CBD 30 mg/Kg repeated administration produced a suppressive effect on hippocampal neurogenesis (DCX). Finally, no significant differences were observed on survival (BrdU) and neurogenesis (DCX) 21 days after the end of CBD repeated treatment.